Influence of lighting and colour usage in higher education, a case study of an architectural studio / Nabilla Ilyana Mohamed Amin and Fazidah Hanim Husain - Mohamed Amin, Nabilla Ilyana; Husain, Fazidah Hanim (2018)
An architectural studio is where architecture students spend a large amount of time to do their respective works. Most of the architectural studios nowadays do not meet the lighting requirement for comfortable working spaces. This case study aims to find out if the architecture studio space in UiTM Cawangan Perak meets the requirements for visual comfort for students in terms of lighting and colour. The architecture studio is evaluated in terms of brightness and colour. The data of brightness in the studio is taken at intervals of two hours for a twelve hour span in a day. The data then is presented in a series of tables and graphs to be reviewed. Colours of the studio are observed and recorded through photographs. After the collected data is calculated through the Lumen method, it is found that the studio does not follow the Malaysian Standard (MS) 1525: 2007 “Code of Practice on Energy Efficiency and use of Renewable Energy for Non-Residential Building.” The lux is too low although the number of luminaires is sufficient. The colour of the studio is also dull which can make the environment boring and unproductive